Lightning Risk Assessment of Distribution Network Line Based on Information Fusion - Zixiang PEI; Kai SHU; Xuntian ZHOU; Tiancheng FAN; Yuhe LUO; Yuting LIU (Zhongguo dianli)
Lightning seriously affects the safe operation of distribution network lines. A lightning risk assessment method based on information fusion is thus proposed by introducing sensitive factors and vulnerability indexes. Firstly, a lightning risk assessment index system is constructed from five aspects including ground resistance, population density, tower height, river network density and slope direction. Secondly, by introducing the analytic hierarchy process of information fusion, a correlation matrix of lightning damage is established based on grey, entropy weight and evidence theory to carry out comprehensive evaluation. Finally, a case study of a distribution network line was conducted. The results show that the evaluation results of the proposed method are basically consistent with the actual results for overall trend of lightning risk, which validates the rationality of the index system.